Segmental hair mercury evaluation of a single family along the Upper Madeira Basin, Brazilian Amazon Avaliação de mercúrio em segmentos de cabelo dos indivíduos de uma única família residente na Bacia do Alto Madeira, Amazônia Brasileira - Ana Amélia Peixoto Boischio; Elsa Cernichiari; Diane Henshel (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
Mercury pollution (MeHg) up the aquatic food chains in the Amazonian ecosystems has been a major concern in environmental health. Riverside people (ribeirinhos) along the Upper Madeira river are heavy fish eaters. Hair is the best biomarker for MeHg exposure. By assuming a constant hair growth rate, it is possible to evaluate a temporal profile of Hg exposure over the recent defined past. In this paper we present the segmental total hair Hg concentrations from a single family from which some of the 10 persons investigated had high hair Hg concentrations (peak of 339 ppm). We also presented the hair MeHg content from 4 out of the 10 family members investigated. There was a wide variation in total hair Hg concentrations (8 to 339 ppm) among these individuals, who were mostly sharing their meals; there was also a wide variation in total Hg concentrations in the same individual over time (136 to 274 ppm). Hg speciation showed a mean and standard deviation in the MeHg content of 62% and 6%, respectively. The wide variation in total hair Hg concentration strongly indicated that it is possible to mitigate critical Hg exposure levels by conducting a fish advisory. A poluição por mercúrio orgânico (MeHg) das cadeias alimentares aquáticas nos ecossistemas amazônicos constitui tema de relevância na saúde ambiental. O MeHg pode chegar às populações humanas mediante o consumo de peixe. Os ribeirinhos do Alto Madeira consomem grandes quantidades de peixe. O cabelo é o melhor biomarcador para exposição ao MeHg; é possível também assumir uma taxa constante de crescimento do cabelo, para verificar o comportamento das exposições no passado recente. Neste trabalho apresentamos as concentrações de Hg total (máxima de 339 ppm) em segmentos de 3 cm de cabelo de dez pessoas de uma única família. Apresentamos também os percentuais de MeHg nas amostras de cabelo de quatro pessoas, dentre as dez em estudo. Nessa família, foi observada uma grande variação na concentração de Hg total (8 a 339 ppm) no cabelo de pessoas que repartiam suas refeições no mesmo domicílio. Foi também observada uma grande variação de Hg total (136 a 274 ppm) nos diversos segmentos de cabelo da mesma pessoa. A especiação de Hg mostrou média e desvio padrão do conteúdo de MeHg de 62% e 6%, respectivamente. As variações das concentrações de Hg em cabelo sugerem ser possível prevenir exposições críticas através de recomendações de consumo de peixe.